National trends in inpatient rehabilitation utilization among patients with sepsis in Japan: a nationwide cohort study from 2010 to 2020 by the Japan Sepsis Alliance (JaSA) study group - Taro Imaeda; Yusuke Kawamura; Takehiko Oami; Tatsuro Yokoyama; Satoshi Nakagawa; Hiroshi Ogura; Nobuaki Shime; Yutaka Umemura; Asako Matsushima; Kiyohide Fushimi; Taka-aki Nakada (BMC Health Services Research, 2026)
Abstract Background Rehabilitation is increasingly recognized as an essential component of recovery for patients with sepsis. However, the real-world delivery of rehabilitation services for sepsis has not been characterized at a national level. This study aimed to evaluate temporal trends and patterns in the utilization and delivery of inpatient rehabilitation among patients hospitalized with sepsis in Japan. Methods This nationwide retrospective cohort study used the Japanese Diagnosis Procedure Combination database from 2010 to 2020. Adult patients (≥ 18 years) hospitalized with sepsis were identified using criteria for presumed serious infection and acute organ dysfunction. Outcomes included annual trends in rehabilitation utilization, specifically implementation rate, initiation timing, duration, and proportion of hospital stay with rehabilitation. Temporal trends were evaluated using Cochran-Armitage trend tests, linear regression analyses, and multivariable modified Poisson regression analyses adjusted for patient characteristics, comorbidity burden, and treatment intensity indicators. Analyses were stratified according to survival status, with subgroup analyses according to age, intensive care unit (ICU) admission, and septic shock. Results Among 4,426,342 sepsis hospitalizations, 2,251,329 (50.9%) involved rehabilitation. Hospitalizations involving rehabilitation were characterized by older patient age and more frequent use of intensive care treatments, such as mechanical ventilation, vasoactive drugs, and renal replacement therapy. The rehabilitation implementation rate increased from 25.2% in 2010 to 68.2% in 2020, and these trends remained significant after multivariable adjustment. Median initiation time decreased from 8 to 4 days, median duration decreased from 18 to 13 days, and the proportion of hospital stay with rehabilitation increased from 41.7% to 51.0%. These temporal patterns were consistent regardless of survival. Subgroup analyses showed higher rehabilitation implementation rates among hospitalizations involving older individuals, ICU admission, or septic shock. Hospitalizations involving ICU admission or septic shock also had longer rehabilitation durations. Conclusions The delivery of inpatient rehabilitation for patients with sepsis in Japan changed substantially between 2010 and 2020, with earlier initiation and broader implementation across clinically relevant subgroups. These findings provide nationwide evidence describing real-world rehabilitation service delivery in sepsis care and may inform healthcare planning and resource allocation for recovery-oriented care.